Evaluation of Heavy Metal Contamination in Amaranthus hybridus (Spinach) - Titus, Stephen D.; Apollos, Markus R.; John, Senufa; Usman, Patricia G.; Garba, Liatu C (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
Heavy metals contamination in edible plants poses significant risks to human health and environmental sustainability. This study evaluates heavy metal contamination in Amaranthus hybridus L. (spinach) collected from three sites: Nyabunkaka River, Kogin Sarki, and Mayo-Gwoi River in Jalingo, Taraba State, Nigeria. The study aimed to determine the levels of lead (Pb), cadmium (Cd), chromium (Cr), zinc (Zn), copper (Cu), nickel (Ni), manganese (Mn), and cobalt (Co) in spinach samples using Atomic Absorption Spectrophotometry (AAS). Results revealed that Pb concentration in spinach from Nyabunkaka slightly exceeded the FAO permissible limit, while Cd, Cr, Zn, Cu, Ni, Mn, and Co levels in all samples were below FAO reference values, indicating minimal contamination risks. These findings highlight the potential environmental pollution near Nyabunkaka River and suggest that spinach from the selected areas remains largely safe for human consumption, except for slight Pb contamination. The study emphasizes the need for continuous monitoring to ensure food safety.